Reproduction in South American wild canids—A review - Carvalho, Jaqueline Candido de; Souza, Fabiana Ferreira; Kastelic, John Patrick; Ferreira, João Carlos Pinheiro (Frontiers in Veterinary Science, 2022)
Canids occupy the top of the food chain and are fundamental in sustaining a wild animal/environmental balance. South America, the most biodiverse continent, has 11 species of canids inhabiting diverse biomes, with or without overlapping territories. Although several species are threatened, little is known about their reproductive biology. Remarkably, basic knowledge regarding ejaculate characteristics, sexual behavior, female reproductive cycles, pregnancy and management, and parturition are scarce or absent. These gaps complicate or preclude development of conservation programs. This review compiles the current knowledge of the reproductive biology of South American canids and discusses implications of this scenario.